Patrography and compositional characteristics of Ewekoro formation, eastern Dahomey basin, southwestern Nigeria: implications for depositional environment and reservoir characteristics (2013)
Subsurface samples of the predominantly carbonate Ewekoro foundation, obtained from the Ibese core hole, in the eastern Dahomey Basin, were examined based on petrographic and geochemistry indices. The study aims at ascertaining the microfacies, depositional environment, as well as the reservoir characteristics. Petrographic reveals sandy biomicrite, biomicrite, biosparite and dolomitic microfacies with fossil content made up of gastropods, brachiopods, ostracods, coralline algae and foraminifera. It is observed that the depositional porosity has been altered by different diagenetic pore types which could serve as conduits for fluids. Major element oxides ranges; CaO (39.79-53.98wt. %), SiO2 (1.29-25.37 wt. %), AI2O3 (0.43-3.77 wt. %) K2O (0.04-0.27wt. %)Fe2O3 (0.74-2.35wt. %), and Na2O (<0.01-0.05 wt. %). Correlation coefficient shows that elements such as Na, K, Ti, Ba, Cs, Ga, Rb, Sr, Th, La, Ce, Mo, and Ni have strongly correlated values with Al (r >0.75). Consequently, they share siliciclastic origin with abundance of Al and their fluctuations can be linked to variation in detrital influx. The U/Th ratio (-0.25 to 2.3) and the V/Sc ratio (-6.0 to 23) suggest that the Ewekoro limestone was deposited in an oxic to anoxic setting with a strong anoxic influence.